Feasibility of a community‐based cervical cancer screening with "test and treat" strategy using self‐sample for an HPV test: Experience from rural Cameroon, Africa. Issue 1 (9th November 2019) - Fokom Domgue, Joel; Futuh, Beatrice; Ngalla, Calvin; Kakute, Peter; Manjuh, Florence; Manga, Simon; Nulah, Kathleen; Welty, Edith; Schmeler, Kathleen; Welty, Thomas
Abstract : To achieve higher coverage and effectiveness in limited‐resource settings, World Health Organization (WHO) guidelines for cervical cancer prevention recommend a screen‐and‐treat strategy with high‐risk human papillomavirus (HPV) testing. We piloted a real‐word project to examine the feasibility of this approach in rural Cameroon. Nurses from the Women's Health Program (WHP) of the Cameroon Baptist Convention Health Services (CBCHS) educated women in remote villages on cervical cancer prevention. At a follow‐up visit, they explained to nonpregnant women aged 30–65 how to self‐collect vaginal specimens for HPV testing with the careHPV assay. The cytobrush specimens were transported in coolers to a CBCHS laboratory for analysis. The nurses returned to villages to inform women of their results, examined HPV‐positive women in the primary health centers (PHCs) using visual inspection with acetic acid and Lugol's iodine (VIA/VILI) enhanced by digital cervicography (DC) to guide treatment. Of the 1, 270 eligible women screened (mean age: 44.7 years), 196 (15.4%) were HPV‐positive, of whom 185 (94.4%) were examined, 16 (8.6%) were VIA/VILI‐positive, 8 (4.3%) were VIA/VILI‐inadequate, one (0.5%) was VIA/VILI‐uncertain and 161 (87.0%) were treated with thermal ablation. One woman had LEEP, and another woman with invasive cancer was treated at a referral facility. The cytobrushes broke off in the vaginas of two women (removed in the village) and in the bladder of another (surgically removed). Community‐based cervical cancer screening with self‐collected specimens for HPV testing is feasible in rural Cameroon. Education on the proper sampling procedure and follow‐up of women who are HPV‐positive are essential. Abstract : What's new? In Africa, the continent with the highest burden of cervical cancer globally, nearly three quarters of cases occur in rural areas. Per the World Health Organization, HPV‐based screen‐and‐treat is a preferred strategy for cervical cancer secondary prevention in limited resource settings. However, the successful implementation of this recommendation in rural and remote areas of Africa remains uncertain. Here, the authors designed and piloted a culturally appropriate screening strategy with self‐collected HPV testing, and found that community engagement is critical to achieve success. In particular, education on the proper sampling procedure and follow‐up of women who are HPV positive are essential.